Ethnobotany of traditional medicinal plants used by Dayak Desa Community in Sintang, West Kalimantan, Indonesia - MARKUS IYUS SUPIANDI; SUSRIYATI MAHANAL; SITI ZUBAIDAH; HENDRIKUS JULUNG; BENEDIKTUS EGE (Society for Indonesian Biodiversity, 2019)
Abstract. Supiandi MI, Mahanal S, Zubaidah S, Julung H, Ege B. 2019. Ethnobotany of traditional medicinal plants used by Dayak Desa Community in Sintang, West Kalimantan, Indonesia. Biodiversitas 20: 1264-1270. Dayak Desa community has a long history of using medicinal plants as one of the methods to overcome health problems. Along with the advancement of science, the influx of foreign cultures and environmental degradation, traditional knowledge about medicinal plants and their utilization are only owned by the old generation. This study, therefore, aimed to identify medicinal plants used by Dayak Desa community who lives in Pakak Village. To collect information from the community, a survey was conducted in June 2017. Snowball sampling method was utilized to select 6 informants from whom information related to the plants’ local names, the used parts of the plants, and the ways of managing and using the plants for curing illnesses was obtained through structured interviews. Data analysis was qualitative and quantitative. The results show that 25 species of medicinal plants from 9 families. The most widely used part of the plants is the leaves. The people in the community boil the leaves and drink the extract. Based on the results of the ICS analysis, the plant's value ranged from 1 to 24. The highest value was observed in keladi (Colocasia esculenta L.) and the lowest value was found in kayu kenanga (Canangium odoratum Baill).